T9-T10 Osteomyelitis, Epidural Abscess and Cord Compression Secondary to Mycobacterium abscessus: A Case Report - Davis, Michelle A.; Antony, Suresh (Infectious Disorders - Drug Targets, 2021)
Background: We report a case of spinal abscess/osteomyelitis at the T9-T10 levels in a non-immunocompromised patient who presented with lower extremity weakness secondary to a Mycobacterium abscessus infection. This patient was successfully treated with surgical debridement with amikacin-tigecycline-imipenem triple therapy before and after her debridement. Outcomes and treatment with this rare cause of epidural abscess/osteomyelitis are not well defined at this time. Case Report: Clinical Presentations with this species of mycobacterium are usually systemic with patients presenting with pulmonary and soft tissue infections. The primary presentation of spinal epidural abscess/osteomyelitis is unusual, especially when there is no primary focus such as a lung infection or concurrent bacteremia. Conclusion: This paper presents a new case of spinal osteomyelitis without a primary source in addition to 10 previously reported M. abscessus cases. The treatment plans and outcomes suggest that surgical debridement along with a macrolide-based combination therapy should be considered a definitive treatment against Mycobacterium abscesses.
Keywords: Mycobacterium abscessus